PENGARUH KOMPENSASI TERHADAP KOMITMEN ORGANISASI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERASI (Survei Pada Guru di SMA dan SMK Swasta Kecamatan Gondang Sragen) - Lamidi, Iis Wahyu Minarsih, Amin Wahyudi & (Universitas Slamet Riyadi, 2016)
The purpose of this research was: 1) to analyze the significant influence of organizational commitment on compensation against a teacher in high school and Vocational School Private Sub Gondang Sragen. 2) to analyze significant influence motivation work towards organizational commitment on teachers in high school and Vocational School Private Sub Gondang Sragen. 3) to analyze significant influence motivation towards work in compensation for teachers in high school and Vocational School Private Sub Gondang Sragen. 4) to analyze the influence of moderation work on compensation influence motivation towards organizational commitment on teachers in high school and Vocational School Private Sub Gondang Sragen. Research methods method using survey data, the type of data used was qualitative and quantitative data, the source data used the primary data and secondary data. The population in this study all the teachers non civil servants in senior high school and vocational school Private Sub Gondang, Sragen 2015 totaling 54 teachers. As for the number of samples used in the study was as many as 54 people, so this research is the study of the census. Methods of data collection were used: questionnaires, observation and documentation. Technique of data analysis used the test of validity, reliability test, test the assumption of Linear regression analysis, classic Double, t test, F test, the coefficient of determination and the absolute difference test. The research results obtained conclusions: 1) there is a significant influence on organizational commitment against compensation of teachers in high school and vocational school Private Sub Gondang Sragen. 2) there is a significant influence on the motivation of working towards organizational commitment on teachers in high school and Vocational School Private Sub Gondang Sragen. 3) there is a significant influence on the motivation of working against compensation of teachers in high school and Vocational School Private Sub Gondang Sragen. 4) analysis results obtained the conclusion that work motivation variables cannot moderate the influence of variable compensation against the organizational commitment.Keywords: compensation, organizational commitment, job motivation.